2012
DOI: 10.1055/s-0032-1317380
|View full text |Cite
|
Sign up to set email alerts
|

New Simple Synthesis of Quinoline-4-carbonitriles

Abstract: Alkylation of 2-nitrobenzyl cyanides with α-halomethyl ketones furnishes ketonitriles which upon reduction with tin(II) chloride form quinoline-4-carbonitriles in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Methanesulfonyl and pivaloyl chlorides, in combination with DBU proved ineffective in this reaction giving a very low rate of conversion after 24 h. Thus, transformations of other nitriles 5b – g into pyrrolo[3,2- e ]indoles 6 were performed in the DBU–chlorotrimethylsilane system, and the results are presented in Table 1. It is worth mentioning that the ketone 5d upon reduction with SnCl 2 cyclized to pyrrolo[3,2- f ]quinoline-9-carbonitrile 7 [17]. …”
Section: Resultsmentioning
confidence: 99%
“…Methanesulfonyl and pivaloyl chlorides, in combination with DBU proved ineffective in this reaction giving a very low rate of conversion after 24 h. Thus, transformations of other nitriles 5b – g into pyrrolo[3,2- e ]indoles 6 were performed in the DBU–chlorotrimethylsilane system, and the results are presented in Table 1. It is worth mentioning that the ketone 5d upon reduction with SnCl 2 cyclized to pyrrolo[3,2- f ]quinoline-9-carbonitrile 7 [17]. …”
Section: Resultsmentioning
confidence: 99%
“…23 The role of the presence of electron donating or electron withdrawing substituents on the activity of the TBAT analogue has never been studied with the exception of short remark by Ma ˛kosza et al, which synthesized tetrabutylammonium tris(4chlorophenyl)diuorosilicate and tetrabutylammonium diuorotris(4-methylphenyl)silicate. 24 They found that the latter reagent acts signicantly more quickly than TBAT in uorination of benzyl bromide. 25 We hence wondered how the modication of the phenyl groups in TBAT (4a) with more strong electron donating or electron withdrawing groups will inuence the activity and selectivity of the reagent not only with 2-bromooctane, but also with a larger series of secondary substrates.…”
Section: Introductionmentioning
confidence: 99%